Subtitling Francophone World Cinema: Narratives of Identity, Alterity and Power in Audiovisual Translation - Leveridge, Francesca (2023)
Cinematic representations of multilingualism raise questions about communication and mutual understanding not only between characters in films but also between films and their audiences, for whom it is typically necessary to facilitate access to foreign dialogues through different forms of translation. Where languages are pitted against one another, however, or juxtaposed in ways that serve to reveal and explore tensions and hierarchies between different linguistic, cultural and social groups, translation becomes entangled in issues of identity, alterity and power. This thesis untangles and explores these complex interactions between languages and translation as they arise in the practice of subtitling. Specifically, it asks questions about how subtitling can play an active part in the shaping of identity by mediating differences between the local, the national and the global, and how subtitles intersect with the relations of power that exist between different cultures. In turn, the thesis exposes the semiotic and narrative dynamics that subtitles add to films and considers the implications of these findings for the ways we think of audiovisual translation and of its relationship with creative processes and accessibility practices.